Exogenous Glycine Nitrogen Enhances Accumulation of Glycosylated Flavonoids and Antioxidant Activity in Lettuce (Lactuca sativa L.) - Yang, Xiao; Cui, Xiaoxian; Zhao, Li; Guo, Doudou; Feng, Lei; Wei, Shiwei; Zhao, Chao; Huang, Danfeng (Frontiers in Plant Science, 2017)
Glycine, the simplest amino acid in nature and one of the most abundant free amino acids in soil, is regarded as a model nutrient in organic nitrogen studies. To date, many studies have focused on the uptake, metabolism and distribution of organic nitrogen in plants, but few have investigated the nutritional performance of plants supplied with organic nitrogen. Lettuce (Lactuca sativa L.), one of the most widely consumed leafy vegetables worldwide, is a significant source of antioxidants and bioactive compounds such as polyphenols, ascorbic acid and tocopherols. In this study, two lettuce cultivars, Shenxuan 1 and Lollo Rossa, were hydroponically cultured in media containing 4.5, 9 or 18 mM glycine or 9 mM nitrate (control) for 4 weeks, and the levels of health-promoting compounds and antioxidant activity of the lettuce leaf extracts were evaluated. Glycine significantly reduced fresh weight compared to control lettuce, while 9 mM glycine significantly increased fresh weight compared to 4.5 or 18 mM glycine. Compared to controls, glycine (18 mM for Shenxuan 1; 9 mM for Lollo Rossa) significantly increased the levels of most antioxidants (including total polyphenols, α-tocopherol) and antioxidant activity, suggesting appropriate glycine supply promotes antioxidant accumulation and activity. Glycine induced most glycosylated quercetin derivatives and luteolin derivatives detected and decreased some phenolic acids compared to nitrate treatment. This study indicates exogenous glycine supplementation could be used strategically to promote the accumulation of health-promoting compounds and antioxidant activity of hydroponically grown lettuce, which could potentially improve human nutrition.